2013
DOI: 10.1021/jp403899w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Heavily Adhesive Cs: Why Radioactive Cs is not Decontaminated from Soil

Abstract: Two years having passed since the nuclear crisis at Fukushima, radioactive 137 Cs with a half-life of ∼30 years has come to the forefront of our largest concern. To gain an insight into current unsuccessful 137 Cs decontamination from soil, heavily adhesive Cs adsorption, referred to as specific Cs adsorption here, is highlighted for layered clay minerals. Besides the interlayer Cs + cations, a population of Cs is able to adsorb on the surfaces of open nanospaces with their sizes of ∼0.3 and ∼0.9 nm, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…In that context, clay-water solid/liquid interfaces [3][4][5][6][7][8][9] were frequently investigated for two reasons. First, from a theoretical point of view, clay platelets are flat and atomically smooth with a well-characterized structure and atomic composition, leading to ideal models of solid/liquid interfacial systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that context, clay-water solid/liquid interfaces [3][4][5][6][7][8][9] were frequently investigated for two reasons. First, from a theoretical point of view, clay platelets are flat and atomically smooth with a well-characterized structure and atomic composition, leading to ideal models of solid/liquid interfacial systems.…”
Section: Introductionmentioning
confidence: 99%
“…First, from a theoretical point of view, clay platelets are flat and atomically smooth with a well-characterized structure and atomic composition, leading to ideal models of solid/liquid interfacial systems. Second, natural and synthetic clays are used in a large variety of industrial applications (drilling, heterogeneous catalysis [8], waste storing [9], food, paint and cosmetic industries), exploiting their various physico-chemical properties (gelling, thixotropy, surface acidity, high specific surface and ionic exchange capacity, water and polar solvent adsorption, swelling). Optimizing applications such as heterogeneous catalysis and waste storing requires quantifying the mobility of solvent molecules and neutralizing counterions inside the porous network of clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…These silicates stabilize Cs on the surface and silicate sheets because of their negative charges. In particular, in the case of 2:1-type layer silicates, Cs is strongly adsorbed at frayed edge sites (FESs) [7][8][9][10]. In this context, it is necessary to understand the stabilization mechanism to analyze the structure of Cs in the clay surface, silicate sheet, and FESs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the above-mentioned two nanosheet insertion type local molecular structure, referred to as type B, appearing during self-assembly is associated with a number of global environmental issues [4][5][6]. For example, the characteristic local structures as a nanosheet edge and a wedge-shaped frayed part available in the voids of type B are responsible for site specific Cs adsorption [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the characteristic local structures as a nanosheet edge and a wedge-shaped frayed part available in the voids of type B are responsible for site specific Cs adsorption [4,5]. Pore fluid in this local structure has been suggested to be related to earthquake slip weakening in plate-boundary faults [6].…”
Section: Introductionmentioning
confidence: 99%